ANALISIS VEGETASI HABITAT ANGGREK DI SEKITAR DANAU TAMBING KAWASAN TAMAN NASIONAL LORE LINDU - Febriliani, Febriliani; Ningsih, Sri; Muslimin, Muslimin (Jurnal Warta Rimba, 2013)
The research objective were to analyze the vegetation of orchid habitat and to determine orchids species around Tambing Lake, Lore Lindu National Park area, Sedoa village, Lore Utara district, Poso regency, Central Sulawesi. The study employed survey method. The vegetation was recorded in 20m x 20m plots by using purposive sampling methods in orchid habitat. The collected data include all plant species and growth level swithin the sampling plot. The total observation area was 0,16 ha. The results showed that the total number of tree level of plant species recorded was 38 species comprising 9 families with the highest Importance Value Index (IVI) was 61,62%. The total number of pole level of plant species recorded was 34 species comprising 7 families with the highest IVI was 74, 43%. The total number of sapling level of plant species recorded was 37 species comprising 9 families with the highest IVI was 65,41%. Hence, The total number of seedling level of plant species recorded was 31 species comprising 7 families with the highest IVI was 49,34%. The highest IVI at all growth levels was achieved by Kaha (Castanopsis accuminatisima). In addition, there were 12 orchid species comprising 8 genus founded in this area,i.e; Agrostophyllum, Bulbophyllum, Calanthe, Coelogyne, Dendrobium, Dendrochyllum, Eria, and Trichotosia. Keywords : Vegetation, Orchids Habitat, Tambing Lake, Lore Lindu National Park.